Role of maintenance strategies in advanced epithelial ovarian cancer: a systematic review, network meta-analysis and cost-effectiveness analysis protocol. Issue 12 (30th December 2021) - Hu, Qiancheng; Kang, Wenli; Wu, Qiuji; Wang, Xin; Wang, Qingfeng; Luo, Ting
Abstract : Introduction: Different maintenance strategies have shown efficacy in patients with advanced ovarian cancer, but without drawing any conclusion on which strategy is preferred. Therefore, we will conduct a network meta-analysis and cost-effectiveness analysis to investigate maintenance strategies containing chemotherapy, poly (ADP-ribose) polymerase (PARP) inhibitors and anti-angiogenesis therapy for patients with advanced ovarian cancer. Methods and analysis: The search strategy to identify potentially relevant studies will include hand searches in EMBASE, PubMed, Cochrane library and Web of science. The primary outcome is progression-free survival, defined as the date of randomisation to the date of progression or death. The secondary outcome is overall survival (calculated from the time from randomisation to death from any cause), grade 3–4 haematological and non-haematological toxicities, quality-adjusted life years and incremental cost-effectiveness ratios. Two steps of meta-analysis will be carried out, traditional pair-wise meta-analysis and network meta-analysis. Methodological quality, risk of bias and the strength of evidence from randomised controlled trials (RCTs) will be proposed to assess the quality of RCTs. Heterogeneity, publication bias, subgroup analysis and sensitivity analysis will be explored. Ethics and dissemination: The purpose of our study is to perform a comprehensive efficacy, safety and cost-effectiveness analysis of all maintenance strategies in patients with advanced ovarian cancer. The results will be disseminated through international conference reports and peer-reviewed manuscripts. Ethics approval is not required for network meta-analysis and cost-effectiveness analysis. PROSPERO registration number: CRD42021231814.